Cross-sectional assessment of perception and attitude of pharmacy students towards pharmaceutical promotion: a study from developing country, Pakistan - Gillani, Ali Hassan; Arshad, Hafsa; Arshed, Muhammad; Jairoun, Ammar; Shukar, Sundus; Akbar, Jamshaid; Hussain, Azzah Khadim; Malik, Hafiz Muhammad Abbas; Ibrahim, Mohamed Izham Mohamed; Fang, Yu (Frontiers in Medicine, 2024)
The pharmaceutical promotion is "all informational and persuasive activities by manufacturers and distributors, the effect of which is to induce the prescription, supply, purchase and/or use of medicinal drugs. These promotional activities affect the dispensing behavior of physicians and pharmacists and influence begins from educational institutes.Our study's main aim was to evaluate opinion and attitude of pharmacy students toward pharmaceutical promotion.A significant number of students concurred with the notion that promotional activities could impact dispensing practices and they also believed that such activities contribute to the growing issue of irrational antibiotic use. This study underscores the necessity for a heightened emphasis on the educational needs of pharmacy students.